Antimicrobial residues screening in pigs and goats slaughtered in Nsukka Municipal abattoir, Southeast Nigeria - Ekene V. Ezenduka; Chinyere Ugwumba (African Journal of Pig Farming, 2019)
Antimicrobial residue in animal food products is an important index of food safety. Drug residues could result from chemotherapeutic or chemoprophylactic use of drugs in food animals. This occurrence of residue in animal food products has received enormous worldwide attention from some local, international and public health agencies. Samples of tissues/organs from pigs and goats slaughtered at the Nsukka Municipal abattoir, Southeast, Nigeria were screened for the presence of antimicrobial residues. Samples collected from the muscles, liver and kidney of 40 slaughtered pigs and 40 slaughtered goats were analysed for antimicrobial residues using the four plate agar diffusion method. 12 (30%) of the 40 sampled pigs and 10 (25%) of the 40 sampled goats were positive for antimicrobial residues. In pigs, antimicrobial residues occur more in the kidney, muscle and liver in that order, while in goats they occurred more and equally in kidney and liver than in the muscle. The result of the study clearly suggest that the rampant use of antimicrobial drugs in slaughter animals at the Nsukka municipal abattoir coupled with non-adherence to withdrawal periods is grossly practiced in Nigeria. This study further confirms the need to regulate the use of veterinary drugs in livestock production and to enforce laws guarding against drug residues in food animals